Analisis Kemampuan Berpikir Kritis Siswa pada Kegiatan Pembelajaran Daring Matematika di SDN Cisoga 1 - Nuraeni, Siti; Isrok'atun, Isrok'atun; Sudin, Ali (Jurnal Pena Ilmiah, 2021)
Indonesia is currently facing the Covid-19 pandemic. Learning activities are currently carried out online to avoid the transmission of the Covid-19 virus. However, the demands of the curriculum must be achieved, one of which is the ability to think critically. This study was conducted to determine the analysis of online learning on students' critical thinking skills in mathematics in elementary school. The research method used is descriptive qualitative research method. Through the analysis of interview instruments, tests, and observations with the subject of class V students at SDN Cisoga 1, totaling 29 students. The research data shows that (28%) students are in very good category, and (45%) students in the very poor category. This shows that almost half of the fifth grade students at SDN Cisoga 1 have very poor critical thinking skills. Therefore, the implementation of online learning activities in elementary schools needs to be improved for the better.